Implementasi Total Quality Management (TQM) dalam Meningkatkan Mutu Pendidikan: (Studi Kasus di MTs Salafiyah Syafi'iyah Tebuireng) - Nurul Indana (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2017)
The school challenge is creating qualified human resource who are capable in solving global problems in education. The Total Quality Management (QTM) is a concept of school management in implementing education and it is expected to be able to provide a better change in accordance with the development, the demands and dynamics of society in addressing the problems of education management at the school level. The impelementation steps of Total Quality Management at MTs Salafiyah Syafi``'iyah Tebuireng has fulfilled of Total Quality Management principles. The educational quality of MTs Salafiyah Syafi'iyah in term of input quality, students, teachers, facilities has reached the target. Besides, the teachers have used variety teaching method, so that students can understang the given materials. The out put quality, MTs Salafiyah Syafi'iyah is able to produce excellence either in academic or non-academic. The obstacle factors of MTs salafiyah Syafi'iyah quality is: many programs are launched, so that a specified time often clash with other activities, the centralized financial, not all students stay in boarding school, so the founder can not supervise the students during in hours.